TiO2 coated microfluidic devices for recoverable hydrophilic and hydrophobic patterns - Lee, Jin-Hyung; Kim, Sang Kyung; Park, Hyung-Ho; Kim, Tae Song (IOP PUBLISHING LTD, 2015)
We report a simple method for modifying the surfaces of plastic microfluidic devices through dynamic coating process with a nano-colloidal TiO2 sol. The surface of the thermoplastic, cyclic olefin copolymer (COC) was coated with the TiO2 film, that displayed an effective photocatalytic property. The hydrophilic surface is obtained in the TiO2-coated zone of a microfluidic channel, and TiO2 coated surface degradation can be reversed easily by UV irradiation. The present work shows a photocatalytic activity concerning the effect of TiO2 coating density, which is controlled by the number of coating cycles. The hydrophilized surface was characterized by the contact angle of water and the TiO2 coated COC surface reduced the water contact angle from 85 degrees to less than 10 degrees upon UV irradiation. The photocatalytic effect of the layer that was coated five times with TiO2 was excellent, and the super-hydrophilicity of the TiO2 surface could be promptly recovered after 10 months of storage at atmospheric conditions. The COC microfluidic devices, in which TiO2 has been freshly deposited and aged for 10 months, were capable of generating water-in oil-in water (W/O/W) double emulsions easily and uniformly by simple control of the flow rates for demonstration of excellent hydrophilic patterning and recovery of the TiO2 coated in the microchannels.
Keywords: THIN-FILMS; SURFACE MODIFICATION; PHOTOCATALYTIC ACTIVITY; TEMPERATURE; POLYMER